1996
DOI: 10.2337/diab.45.3.s14
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Cardiovascular Disease in a Prospective Population Survey in Japan: The Hisayama Study

Abstract: To elucidate the effect of glucose intolerance on cardiovascular disease in the current Japanese population, we performed a 75-g oral glucose tolerance test in 2,427 Hisayama residents aged 40-79 years in 1988, who were free from a previous history of stroke or myocardial infarction, and followed them prospectively for 5 years. The prevalence of diabetes (NIDDM) among men was 13% and that of impaired glucose tolerance (IGT) was 20%; the corresponding values for women were 9 and 19%, respectively. The age- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
147
4
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(164 citation statements)
references
References 4 publications
11
147
4
2
Order By: Relevance
“…28 The rate of severe obesity (body mass index greater than 35 kg/m 2 ) in patients of North America and Europe is higher than Japanese patients, and Kouchoukos et al 29 reported 18.6% (274 of 1566) severe obesity in CABG patients at Washington University in the United States, whereas severe obesity was only 0.4% (4 of 1131) in our study. Diabetic patients in Japan are rather thin, and this racial difference may influence the prognosis of ischemic heart disease in diabetic patients.…”
Section: Endo Et Al Bilateral Imas For Diabetes 1347contrasting
confidence: 45%
“…28 The rate of severe obesity (body mass index greater than 35 kg/m 2 ) in patients of North America and Europe is higher than Japanese patients, and Kouchoukos et al 29 reported 18.6% (274 of 1566) severe obesity in CABG patients at Washington University in the United States, whereas severe obesity was only 0.4% (4 of 1131) in our study. Diabetic patients in Japan are rather thin, and this racial difference may influence the prognosis of ischemic heart disease in diabetic patients.…”
Section: Endo Et Al Bilateral Imas For Diabetes 1347contrasting
confidence: 45%
“…Various studies have shown the harmful effect of arterial hypertension, dysplipidemia, and diabetes mellitus on the circulatory system; these same diseases have insulin resistance in common and comprise the metabolic syndrome 41 . Other cohort studies on Asian populations have indicated that pre-diabetic individuals have an increased risk of both all-cause and cardiovascular mortality 42,43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the question of whether a casual blood glucose (CBG) level, whose value can be obtained at any time of the day regardless of time since last meal, can predict CHD or CVD mortality is of great interest. Only one prospective study has reported this relationship between CBG and CHD [6], though some prospective studies have reported the relationship between CHD and fasting blood glucose or OGTT [7][8][9]. We investigated the relationship of CBG with CHD, CVD and all-cause mortality in a 17.3-year follow-up study with a representative sample from the Japanese population.…”
Section: Introductionmentioning
confidence: 99%